Contributing to the development of water-pollution awareness in 11th grade students, Class 4, at “Capitán Roberto Rodríguez” Pre-university School - Pérez Chávez, Jorge David (Universidad Central Marta Abréu de las Villas. Facultad Media Superior, 2020)
The objective of this major paper is to propose a system of lessons and project works to increase water pollution awareness in 11th graders at “Capitan Roberto Rodriguez” Pre-university School in Santa Clara. This study highlights the importance of including environmental education in the English curriculum. The students’ strengths and weaknesses were assessed through the administration of different empirical methods such as interview, survey, document analysis. The results revealed that although the sample of students had some knowledge on environmental issues, they showed unawareness on the role they can play in reducing environmental problems. Accordingly, a system of lessons was designed to meet such needs. The proposal was submitted to the criteria of the specialists of the Department of Foreign Languages, from Varela Campus and teachers of English of the General System of Education who evaluated its quality, pertinence, and feasibility. In addition, they offered some suggestions that were essential to the improvement of the proposal.
Keywords: Educación Superior; Enseñanza del Inglés; Didáctica del Idioma; Lenguas Extranjeras; Educación Ambiental; Educación; Educación Ambiental en Cuba